Analysis of Financial Accountability through E government in West Java Province, Indonesia - erdania Latif, Dini V; Roespinoedji, Djoko; Ali, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Financial accountability refers to controlling the use of financial resources properly. The government must be responsible for the public funds it manages. Receipts and disbursements of public funds must be in accordance with the law. Therefore, to ensure accountability, the government must provide information needed by the public for monitoring. This study aims to examine financial accountability through e government. Content analysis is used to examine whether the e government has fulfilled the content related to accountability or not. The research sample is 27 e government of municipal and district in West Java, Indonesia. The results showed that e government in the West Java region has not shown satisfactory results. Of the 27 websites studied, only 5 websites met accountability requirements. Even so, the public in the region has never claimed their right to disclose public information. This can happen because the public does not really understand their rights. For this reason, it is important to be socialized about the importance of government accountability to the public.